1990
DOI: 10.1007/bf01849490
|View full text |Cite
|
Sign up to set email alerts
|

Spermicides, hormonal contraception and congenital malformations

Abstract: Allegations that inadvertent pregnancies in contraceptive users are associated with congenital anomalies continue to be common. In 1985, a review by one of us concluded that there is little or no scientific basis for such claims [1]. Since then, additional data have substantiated this conclusion, particularly with respect to spermicides and hormonal contraception. The purpose of this review is to update information with respect to potential teratogenicity for these two contraceptive methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 81 publications
(115 reference statements)
1
9
0
Order By: Relevance
“…Others had used barrier method mostly where the association might be due to usage of spermicidal agents. 26,27 In our study, history of any drug usage during pregnancy was also found to be significantly associated with CMF (adjusted and 6 years, the ratio was 1.3:1 in malformed babies. The higher representation of males in our study may be related with skewed sex ratio in Haryana and Punjab due to a high incidence of sex selective abortions in this region.…”
Section: Agarwalsupporting
confidence: 55%
“…Others had used barrier method mostly where the association might be due to usage of spermicidal agents. 26,27 In our study, history of any drug usage during pregnancy was also found to be significantly associated with CMF (adjusted and 6 years, the ratio was 1.3:1 in malformed babies. The higher representation of males in our study may be related with skewed sex ratio in Haryana and Punjab due to a high incidence of sex selective abortions in this region.…”
Section: Agarwalsupporting
confidence: 55%
“…Clinical data have not verified other theorized mechanisms of action that may be involved, such as preventing implantation, altering sperm or egg transport, inhibiting the fertilization process, or changing cervical mucous. Accidental use of ECPs during pregnancy will neither interrupt a pregnancy after implantation nor be teratogenic [11][12][13]. The predominant side effects associated with use of combination ECPs are nausea (51%) and vomiting (19%) [7].…”
Section: Introductionmentioning
confidence: 99%
“…ECPs will not interrupt or harm an established pregnancy. Several studies involving the long-term use of OCPs have not shown any teratogenic effects on the fetus [11][12][13]. For combination ECPs, some health care providers use the same contraindications as for ongoing use of hormonal contraceptives containing estrogen such as history of thromboembolism, ischemic heart disease, uncontrolled hypertension, or hypersensitivity to any of the components.…”
Section: Introductionmentioning
confidence: 99%
“…If vomiting occurs within 2 hours, the dose should be repeated [18]. ECPs have been found not to harm or disrupt an established pregnancy [27][28][29].…”
Section: Prevention and Management Of Pregnancy After Rapementioning
confidence: 99%